2015
DOI: 10.1007/s00044-015-1448-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 4-hydroxycoumarin derivatives: evaluation of antimicrobial, antioxidant activities and its molecular docking studies

Abstract: A series of novel 4-hydroxycoumarin derivatives 4a-n were synthesized by treating 2-(2-oxo-2H-chromen-4-yloxy)acetic acid 3 with various amines. Acid 3 was obtained from the hydrolysis of corresponding ester 2 which was prepared from 4-hydroxycoumarin 1 and ethyl bromoacetate. All synthesized compounds 4a-n were characterized using spectral techniques. The synthesized compounds 4a-n were evaluated for their antimicrobial and total antioxidant activity using in vitro well diffusion method and phosphomolybdenum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Coumarin (2-oxo-2H-chromene) is a naturally occurring heterocyclic compound isolated from various plants; it has been found in the microorganisms, animals, essential oils, and fruits [4,[7][8][9][10][11][12]. N-(diphenylmethyl)-2-[(2-oxo-2Hchromen-4-yl)oxy]acetamide (Figure 1(b), already reported by Govindhan et al) [13] which originates from 4-hydroxycoumarin shows the functional biological activity and also the more biologically active site of the coumarin family make more interest on, to understand the pharmacokinetic mechanism into the carrier molecule.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Coumarin (2-oxo-2H-chromene) is a naturally occurring heterocyclic compound isolated from various plants; it has been found in the microorganisms, animals, essential oils, and fruits [4,[7][8][9][10][11][12]. N-(diphenylmethyl)-2-[(2-oxo-2Hchromen-4-yl)oxy]acetamide (Figure 1(b), already reported by Govindhan et al) [13] which originates from 4-hydroxycoumarin shows the functional biological activity and also the more biologically active site of the coumarin family make more interest on, to understand the pharmacokinetic mechanism into the carrier molecule.…”
Section: Introductionmentioning
confidence: 82%
“…-chromen-4-yl)oxy]acetamide is newly synthesized, which is already reported by Govindan et al [13], and the same drug was dissolved in 0.5% DMSO in the PBS buffer. Human serum albumin was purchased from Sigma-Aldrich, USA, and used without any further purification.…”
Section: Reagents N-(diphenylmethyl)-2-[(2-oxo-2hmentioning
confidence: 99%
“…Many of these compounds have proven to be active as antibacterial, antifungal, anti-inflammatory, anticoagulant, anti-HIV and antitumor agents. One of the title compounds, 2-(4-{2-[(2-oxo-2H-chromen-4-yl)oxy]-acetyl}piperazin-1-yl)acetamide (I), has been shown to exhibit antimicrobial as well as antioxidant activity (Govindhan, Subramanian, Chennakesava Rao et al, 2015;Govindhan, Subramanian, Sridharan et al, 2015). In view of the importance of their natural occurrence, biological activities, pharmacological and medicinal activities, and utility as synthetic intermediates, we have synthesized the title 2-[(2-oxo-2H- chromen-4-yl)oxy]acetamide derivatives, and report herein their crystal structures and Hirshfeld surface analysis.…”
Section: Chemical Contextmentioning
confidence: 99%
“…It is well-known that 4-hydroxychromen-2-one is a star molecule. To date, a large number of studies have demonstrated that it has a wide range of biological activities 15 17 including antioxidant activity, 14 antibacterial activity, 15 and anti-cancer activity. 16 Moreover, a lot of classical organic synthetic reactions have showed that acetone can smoothly react with aniline to generate the electron-rich iso -propenylphenylamine or iso -propylidenephenylamine.…”
Section: Introductionmentioning
confidence: 99%